Full-scale trials to achieve low total phosphorus in effluents from sewage treatment works. (April 2021) - Alibardi, Luca; Vale, Peter; Bajón Fernández, Yadira
Abstract: The tightening of phosphorus (P) standards has forced the UK water industry to identify options to improve P removal in sewage treatment works. This article presents results of 12-month trials testing three technologies at full-scale: a membrane bioreactor (MBR), a continuous backwash up-flow sand filter (CBUSF) and a high-rate compressible media filter (HRCMF). The aim of the trial was to determine the lowest total phosphorus (TP) concentrations that these systems can consistently achieve under stable operating conditions. MBR is a mature technology combining biological treatment with membrane filtration for solids removal. CBUSF uses granular media deep filtration as removal process while HRCMF uses a synthetic fibre compressible media to retain solids and both technologies are typically applied as tertiary treatments in combination with chemical P removal. The lowest TP effluent concentration was recorded for CBUSF (0.22 mg P/L) while the highest TP removal was recorded for MBR (95 ± 3 %). HRCMF delivered the poorest performance (32 ± 26 % TP removal, 1.7 mg P/L average TP effluent), attributed to limited chemical TP binding and solids removal under the conditions tested. Factors affecting P removal performance during the trial were the identification of the optimal coagulant dose to bind soluble P, the formation of solids that can be removed by the separation unit, insufficient reaction time for the coagulation process and the carryover of coagulant into the final effluent. The trials gave valuable insights to address the implementation of new technologies or upgrade existing assets' performance.